The Effect of Adding Coconut Dregs (Cocos nucifera L.) on “Wajik” Characteristics - Sayuti, Kesuma; Syukri, Daimon; Padilah, Rahmi (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2024)
This study aims to determine the effect of adding coconut dregs on the characteristics of wajik based on organoleptic and chemical tests. The research design used was a Completely Randomized Design (CRD) with 5 treatments, namely A (without adding coconut dregs), B (addition of 1% coconut dregs), C (addition of 2% coconut dregs), D (addition of 3% coconut dregs), and E (addition of 4% coconut dregs) with 3 replications. The research data were statistically analyzed using Analysis of Variance (ANOVA) and continued with Duncan's New Multiple Range Test (DNMRT) analysis at the 5% level. The results showed that adding coconut dregs had a significant effect on, fat content, crude fiber, sucrose, total energy, and organoleptic including color, aroma, taste, and texture. However, it had no significant effect on ash content. The best treatment was wajik with the addition of 3% coconut dregs, with ash content of 0.78%, fat content of 14.31%, protein content of 2.58%, crude fiber of 6.42%, total energy of 329.51 kcal, and a liking level for color 3.80 (like), aroma 3.84 (like), taste 3.60 (like), and texture 3.80 (like).